CO2 catalytic conversion catalyst as well as preparation method and application thereof
By using a catalyst supported on a silicon-aluminum composite oxide carrier to support CuO and additives in the CO2 reverse water-gas shift reaction, the problems of poor catalyst stability at high temperatures and high cost of precious metals have been solved, achieving low-temperature and high-efficiency CO2 conversion and CO selectivity, which is suitable for industrial applications.
Patent Information
- Application Number
- CN202411822693.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-12-12
AI Technical Summary
Existing CO2 reverse water-gas shift catalysts are prone to sintering and agglomeration at high temperatures, resulting in poor stability. Furthermore, the high cost of precious metal catalysts limits their large-scale industrial application, and the CO2 conversion rate and selectivity need to be improved.
Using a silicon-aluminum composite oxide as a support, supported CuO is used as the first active component, Mn and/or Fe oxides are used as the second active component, and Ce, Zr or Zn oxides are used as promoters. The activity and stability of the catalyst are improved through synergistic effect. The preparation process is simple and low cost.
The catalyst achieves high CO2 conversion and CO selectivity at low temperatures, exhibits good stability under high temperature and humidity conditions, is suitable for industrial applications, and reduces production costs.
Smart Images

Figure CN119281315A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to CO 2 The technical field of reverse water-gas shift reaction relates to a CO 2 Catalytic conversion catalyst and its preparation method and application. Background Art
[0002] In order to better achieve carbon peak and carbon neutrality, the key is to 2 At present, CO 2 The main ways of conversion and utilization include: CO 2 Methanation, CO 2 Methanol, CO 2 Reverse water gas shift (RWGS). Methanol, as an important chemical raw material, is widely used in the synthesis of many fine chemicals such as olefins. In addition, methanol itself is also a green fuel that can be mixed with gasoline. It has the advantages of high combustion energy release, easy storage, and no environmental pollution components such as sulfur and nitrogen. Therefore, CO 2 Methanol production has become the most promising CO 2 One of the ways to transform and utilize.
[0003] CO 2 The main ways to produce methanol are: direct CO 2 Methanol, CO 2 Reverse water gas shift to indirect methanol production. 2 Direct methanol production is limited by thermodynamic equilibrium and is in the range of 200~300 o C, under high pressure (5-10MPa), CO 2 The equilibrium conversion rate is 20%~30%, and the equilibrium yield of methanol is less than 21%; 2 The indirect method of producing methanol is to convert CO 2 It is converted into CO through the reverse water gas shift reaction, and then CO, CO 2 and H 2 Synthesize methanol, this method can break through the thermodynamic equilibrium limit, CO 2 The equilibrium conversion rate is ≥45%, and the equilibrium yield of methanol is ≥40%. 2 Indirect methanol production is more conducive to CO 2 The improvement of utilization efficiency and methanol yield will bring more significant economic benefits.
[0004] CO 2 The key to indirect methanol production is CO 2 The reverse water-gas shift process is an endothermic process, and high temperature is conducive to CO 2However, high temperature conditions can easily lead to deactivation behaviors such as catalyst agglomeration, sintering of active components, and carbon deposition, resulting in reduced catalytic efficiency. At the same time, due to the endothermic nature of the reaction, it is difficult to obtain high CO under mild conditions. 2 conversion rate, and CO is easily generated at low temperatures 2 Methanation reaction leads to a decrease in CO selectivity. Therefore, a CO 2 Reverse water gas shift catalyst is a catalyst for CO 2 The key to large-scale industrial application of indirect methanol production.
[0005] Chinese patent application CN106881082A discloses a 0.1% Ir / TiO 2 Catalyst, in H 2 / CO 2 =1, 600 °C, 50000 mL / h·g cat Under the conditions of 2 The conversion rate is 30% and the CO selectivity is 96%. CN 108144637 B discloses a 0.5% Pt-KOH / KLTL catalyst. 2 / CO 2 =1, 500 °C, 3000 h -1 Under the conditions of 2 The conversion rate is 27% and the CO selectivity is 100%. Another Chinese patent application CN111250121A discloses a 1% Pd / MoC catalyst in H 2 / CO 2 =4, 400℃, 4560 mL / h·g cat Under the conditions of 2 The conversion rate is 33% and the CO selectivity is 95%. CN 110756197 B discloses a Ni@Au / SiO 2 Catalyst, in H 2 / CO 2 =3, 500 °C, 60000 mL / h·g cat Under the conditions of 2 The conversion was 17.8% and the CO selectivity was 100%.
[0006] The above patents all use precious metals as active components, but CO 2 The conversion rate needs to be improved, and the expensiveness of precious metal catalysts limits their large-scale industrial application.
[0007] Currently, for CO 2The non-precious metal catalysts used in the reverse water-gas shift reaction are mainly copper-based catalysts. For example, Chinese patent application CN107497439A discloses a 10% Cu-CeO 2 Catalyst, in H 2 / CO 2 =1, 600 °C, 6000 mL / h·g cat Under the conditions of 2 The conversion rate was 31.79%. 2 The conversion rate needs to be improved, and there is no data on CO selectivity. After 450 min of continuous reaction, the CO on the catalyst 2 The conversion rate dropped by 12%, and the stability was poor. CN 103230799A discloses a CuZnK catalyst, H 2 / CO 2 =3, 400 °C, 5000 h -1 Under the conditions of 2 The conversion rate was 30.3%, the CO selectivity was 89.2%, and alcohol and CH 4 , oxygen-containing compounds and other by-products. The accumulation of by-products eventually leads to a decrease in catalyst performance and deactivation. Therefore, the CO selectivity and catalyst stability on the catalyst need to be improved.
[0008] Currently, in CO 2 In the reverse water gas shift reaction, copper-based catalysts have been widely studied due to their low price, good low-temperature activity, and high CO selectivity. However, since this reaction is an endothermic reaction, high temperature is conducive to improving catalytic activity. However, under high temperature and strong reducing atmosphere, copper-based catalysts are prone to sintering and agglomeration, resulting in poor high-temperature stability. Therefore, it is necessary to develop copper-based CO catalysts with high activity, high selectivity and / or high stability. 2 Reverse conversion catalyst is to achieve CO 2 The key to the industrial application of indirect methanol production. Summary of the invention
[0009] The purpose of the present invention is to provide a CO 2 Catalytic conversion catalyst and its preparation method and application to further improve its performance in CO 2 Activity, selectivity and stability in the reverse water-gas shift reaction.
[0010] The purpose of the present invention can be achieved by the following technical solutions: In a first aspect, the present invention provides a CO 2 The preparation method of the catalytic conversion catalyst comprises the following steps: (1) Weigh a silicon source and an aluminum source to prepare a silicon-aluminum aqueous solution, mix it with an inorganic acid aqueous solution, and stir to form a white sol until the viscosity reaches 1200-2000 mPa·S; (2) centrifuging, washing and drying the sol obtained in step (1) to obtain white silicon-aluminum composite oxide powder, adding a binder and rolling into balls to obtain a silicon-aluminum composite oxide carrier precursor; (3) Weighing a first active component precursor, a second active component precursor and an auxiliary component precursor, dissolving and stirring them with water as a solvent to obtain a mixed solution; (4) The silicon-aluminum composite oxide support precursor in step (3) is immersed in the mixed solution, dried, and calcined to obtain CO 2 Catalytic conversion catalyst.
[0011] Furthermore, the prepared CO 2 The catalytic conversion catalyst includes a silicon-aluminum composite oxide carrier, and a first active component, a second active component and an auxiliary component loaded on the silicon-aluminum composite oxide carrier, wherein the first active component is CuO, the second active component is an oxide of Mn and / or Fe, and the auxiliary component is an oxide of at least one of Ce, Zr or Zn.
[0012] Furthermore, in the silicon-aluminum composite oxide carrier, SiO 2 The mass content is 50% to 96%, and can be 50%, 60%, 70%, 80%, 90%, 96%, etc., or any other value within the above range. 2 O 3 The mass content is 4% to 50%. For example, it can be 4%, 10%, 20%, 30%, 40%, 50%, etc., or any other value within the above range.
[0013] The binder in the present invention is to improve the balling rate and strength of the carrier in the ball rolling forming, and its dosage can be adjusted as needed. Binders are divided into two categories: organic and inorganic. Organic binders are decomposed and removed during the subsequent roasting process, and inorganic binders cannot be completely removed during the roasting process, such as silica sol and aluminum sol, which eventually exist in the form of silicon oxide and aluminum oxide. Since the amount of binder added is very low, the effect on the overall silicon oxide and aluminum oxide content is very small and can be ignored. Exemplarily, the mass ratio of silicon aluminum composite oxide powder to binder is (1:0.005~0.05), and the binder is one or more of silica sol, aluminum sol, bentonite, sodium methyl cellulose, starch, attapulgite, and kaolin.
[0014] Further, the first active component is 1-15% of the mass of the silica-aluminum composite oxide support, and illustratively, it can be 1%, 5%, 7.5%, 10%, 15%, etc., or any other value within the above range; the second active component is 0.5-7.5% of the mass of the silica-aluminum composite oxide support, and illustratively, it can be 1%, 2.5%, 5%, 7.5%, etc., or any other value within the above range; the auxiliary agent component is 0.5-7.5% of the mass of the silica-aluminum composite oxide support, and illustratively, it can be 1%, 2.5%, 5%, 7.5%, etc., or any other value within the above range.
[0015] Furthermore, in step (1), the silicon source is selected from one or more of silica sol, sodium silicate, and silicon oxide powder.
[0016] Furthermore, in step (1), the aluminum source is selected from one or more of aluminum sol, pseudo-boehmite, quick-de-powdering, and alumina powder.
[0017] Furthermore, in step (1), the inorganic acid is one or more of nitric acid, hydrochloric acid or sulfuric acid.
[0018] Furthermore, in step (1), the H + , SiO in silicon source and aluminum source 2 +Al 2 O 3 The molar ratio of the total amount is 0.5~2:1.
[0019] Furthermore, in step (2), washing is performed once or repeatedly for multiple times until the conductivity of the filtrate is lower than 200 μs / cm.
[0020] Furthermore, in step (2), the drying temperature is 100-120°C.
[0021] Furthermore, in step (2), the mass ratio of the white silicon-aluminum composite oxide powder to the binder is (1:0.005-0.05), and the binder is one or more of silica sol, aluminum sol, bentonite, sodium methyl cellulose, starch, attapulgite, and kaolin.
[0022] Furthermore, in step (3), the first active component precursor is copper nitrate.
[0023] Furthermore, in step (3), the second active component precursor is a nitrate of Mn and / or Fe.
[0024] Furthermore, in step (3), the precursor of the auxiliary component is nitrate of Ce and / or Zr.
[0025] Furthermore, in step (4), the impregnation process is specifically as follows: ultrasonic impregnation for 0.5 to 2 h to achieve the desired loading amount.
[0026] Furthermore, in step (4), the drying process is specifically: drying at 100-120°C for 6-12 hours.
[0027] Furthermore, in step (4), the calcination process is specifically as follows: calcination at 350-600°C for 2-6 h.
[0028] The present invention uses silicon-aluminum composite oxide as a carrier, CuO as the first active component, MnO 2 , Fe 2 O 3 etc. as the second active component, CeO 2 、ZrO 2 , ZnO, etc. as additives. The large specific surface area of the carrier increases the dispersion of the active components, reduces the grain size, and helps stabilize the catalyst. During the preparation process, the sol formed between the silicon source and the aluminum source gradually forms a cross-linking effect under stirring conditions, forming a stable Si-O-Al tetrahedral structure that is not available in conventional physical mixing, which makes the carrier have high thermal stability and better water resistance, which helps to improve the stability of the catalyst under high temperature and high humidity conditions. In addition, the SiO 2 With Al 2 O 3 The mutual adjustment between them makes it have moderate alkalinity and a large number of alkaline sites, which helps to promote CO 2 The adsorption of CO with silicon-aluminum composite oxide supports is moderate, thus promoting the 2 Adsorption and catalytic conversion to improve CO 2 Conversion rate. The addition of the second active component forms a synergistic effect between metals, changes the valence distribution of Cu through electronic effects, significantly improves the dispersion of CuO, further reduces the size of CuO grains, and improves the activity of the catalyst. The addition of the additive significantly reduces the reduction temperature of the catalyst and improves the reduction performance of the catalyst. At the same time, the addition of the additive increases the amount of highly dispersed CuO on the surface, improves the low-temperature activity of the catalyst, forms a solid solution structure between the additive and CuO, further improves the dispersion of CuO, reduces the size of CuO grains, effectively stabilizes the active components, and improves the stability of the catalyst.
[0029] The present invention can achieve the following conditions: 2 / CO 2 =1~4, airspeed 3000~24000h -1 Under the condition of low temperature as low as 300 ℃, CO 2The conversion rate (23%) is close to the thermodynamic equilibrium value, and the CO selectivity is close to 100%. 2 / CO 2 =3, airspeed is 24000h -1 Under the conditions of continuous reaction for 500 h, CO 2 The conversion rate (54.73%) is close to the thermodynamic equilibrium value, the CO selectivity is close to 100%, there is no deactivation phenomenon, and it has good low-temperature activity and high-temperature stability.
[0030] In a second aspect, the present invention provides a CO 2 The catalytic conversion catalyst is prepared by the preparation method as described above.
[0031] Furthermore, the specific surface area of the silicon-aluminum composite oxide support is 500-800 m 2 / g, pore volume is 0.4~0.8cm 3 / g, particle strength ≥60 N / particle, particle strength decreases by <10% after 550 ℃ water vapor treatment, and particle breakage rate in liquid water is <1%.
[0032] Furthermore, the specific surface area of the catalyst is 350~650 m 2 / g, pore volume is 0.3~0.7 cm 3 / g, CuO grain size is less than 2nm.
[0033] In a third aspect, the present invention provides a CO 2 Catalytic conversion of CO 2 Application in reverse water gas shift reaction. Specifically, the catalyst of the present invention (0.1~2.0MPa, H 2 / CO 2 =1~4, airspeed 3000~24000h -1 ) At temperatures as low as 300 °C, CO 2 The conversion rate reached 23%, and the CO selectivity was close to 100%. 2 / CO 2 =3, airspeed is 24000h -1 Under the conditions of 2 The conversion rate reached 54.73%, the CO selectivity was close to 100%, and the reaction was continued at 550 °C for 500 h without deactivation.
[0034] Compared with the prior art, the present invention has the following advantages: (1) Compared with the commonly used alumina carrier in industry, the silicon-aluminum composite oxide carrier of the present invention has a larger specific surface area, which helps to improve the dispersion of active components, reduce the grain size of active components, inhibit the aggregation and growth of active components, and improve the stability of the catalyst; compared with the molecular sieve carrier, the relatively large pore size helps the reactants to diffuse in the pores, promotes the increase of reaction rate, and effectively inhibits the accumulation of intermediate products and by-products, thereby improving the stability of the catalyst; in addition, the silicon-aluminum composite oxide carrier has good high thermal stability and excellent water resistance, which helps to improve the stability of the catalyst under high temperature and high humidity conditions. SiO 2 -Al 2 O 3 The alkaline sites are adjusted to have moderate alkalinity and a large number of alkaline sites. 2 A medium-intensity adsorption is formed between the 2 adsorption and catalytic conversion capabilities.
[0035] (2) CO of the present invention 2 Catalytic conversion catalyst, using CuO as the first active component, has good CO 2 Reaction activity and CO selectivity; the introduction of the second active component forms a synergistic effect with the first active component. The electronic effect between the two changes the valence distribution of Cu, which helps to improve the dispersion of CuO, reduce the grain size, effectively inhibit the aggregation and growth of active components, and improve the activity and stability of the catalyst; the introduction of the additive improves the reduction performance of the catalyst, reduces the reduction temperature, increases the amount of highly dispersed CuO on the surface, and increases the low-temperature activity. On the other hand, a solid solution structure is formed between the additive and CuO, which further improves the dispersion of CuO, reduces the CuO grain size, stabilizes the active component, and improves the stability of the catalyst. In addition, the addition of the second active component and the additive promotes the efficient conversion of the reaction intermediates into the target product CO, effectively inhibiting CO 2 The methanation side reaction prevents the intermediate products and by-products from occupying the catalyst surface and blocking the catalyst pores, thereby greatly improving the stability and service life of the catalyst.
[0036] (3) CO of the present invention 2 The catalytic conversion catalyst uses silicon-aluminum composite oxide as a carrier, which is resistant to liquid free water and high-temperature water vapor. In the presence of free water and high-temperature water vapor, the particle strength can maintain more than 90% of the fresh sample, avoiding pulverization and breakage in industrial applications and improving the stability of industrial equipment operation. At the same time, the catalyst has a simple preparation process, low production cost, and significant cost advantages, which is conducive to industrial production and application and has potential industrial application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 is the CO of the carrier in the examples and comparative examples 2 -TPD spectrum; Figure 2 It is the XRD spectra of the catalysts in the embodiments and comparative examples; Figure 3 is the H of the catalyst in the examples and comparative examples 2 -TPR spectra; Figure 4 In-situ infrared spectra of the catalysts in the examples and comparative examples; Figure 5 It is the stability performance of the catalyst in Example 1. DETAILED DESCRIPTION
[0038] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0039] In the following embodiments, each test method is specifically as follows: The nitrogen adsorption and desorption experiment (BET) was carried out on a specific surface area and pore size analyzer (ASAP 2020). The specific test method was as follows: a certain amount of catalyst sample was weighed and N 2 In the adsorption-desorption test, the BET method was used to calculate the specific surface area of the sample, and the BJH model was used to calculate the pore volume and average pore diameter.
[0040] The strength test was carried out on a particle strength tester (DL3-500). The specific test method was as follows: 30 silicon-aluminum composite oxide carriers were taken, and a single sample was placed on the test platform of the particle strength tester. The compressive strength was tested particle by particle, and then the average strength of the silicon-aluminum composite oxide carrier was calculated.
[0041] The test method for the breakage rate in liquid water is as follows: take 500 g of silicon-aluminum composite oxide support, soak it in 500 mL of water for 30 min, observe the particle breakage, and calculate the breakage rate.
[0042] X-ray diffraction (XRD) was used to test the crystal structure of the catalyst. The test method was as follows: the crystal phase of the catalyst was identified using a Japanese Rigaku D / max-RA X-ray diffractometer. The diffractometer detector was a scintillation counter, with characteristic X-rays of the element as the excitation source, Cu Ka rays, monochromatic wavelength λ=1.54056 Å, tube voltage 40 kV, tube current 100 mA, scanning range 5~80 °, and continuous scanning rate 5 ° / min.
[0043] Using H 2 Programmed temperature reduction (H2 -TPR) to test the reduction performance of the catalyst. Test method: Pantech FineSorb-3010D fully automatic chemisorption instrument was used to perform H 2 -TPR test. The program temperature range is 25~500 ℃, and the reducing gas is 10% H 2 +90% Ar mixed gas, flow rate 30mL / min, heating rate 10℃ / min, TCD detection of H during heating process 2 The TPR curve was obtained by changing the mass fraction.
[0044] Using CO 2 Programmed temperature desorption (CO 2 -TPD) to test the basic strength and number of basic sites of the catalyst. Test method: FineSorb-3010D fully automatic chemisorption instrument from Pantech was used to perform CO 2 -TPD test. Weigh 100 mg of catalyst sample, heat it to 250 °C for pretreatment, and then cool it to 100 °C to adsorb CO 2 The chromatographic baseline was stabilized by purging with He (flow rate of 30 ml / min) at 100 °C, and CO was desorbed by programmed temperature increase (100-600 °C). 2 , flow rate 30 mL / min, heating rate 10 ℃ / min, desorption of CO 2 The signal is detected by a thermal conductivity cell detector.
[0045] The instrument model for the in-suit DRIFT test is Nicoletis50 FT-IR, and the in-suit DRIFT test window is CaF 2 The catalyst loading was 100 mg, and the sample was placed in an in-situ cell at 300 °C with 10% H 2 / N 2 The reduction was performed under a 30 mL / min atmosphere for 2 h. After the pretreatment, N 2 (30 mL / min) for 30 min, then switch to the reaction gas 10% CO 2 -40%H 2 -Ar (30 mL / min), 128 scans, 4 cm resolution -1 , the test temperature is 450 °C.
[0046] High temperature qualitative test method for silicon-aluminum composite oxide carrier: a predetermined amount of silicon-aluminum composite oxide particles are loaded into a stainless steel tube fixed bed reactor, water is introduced by bubbling at room temperature, and the fixed bed temperature is maintained at 550 oC, water vapor was continuously introduced for 6 hours, and then the temperature was lowered to room temperature. The silicon-aluminum composite oxide particles were taken out and strength tested. Comparative analysis of 550 o C Changes in particle strength after water vapor treatment.
[0047] The rest of the raw materials or processing techniques, unless otherwise specified, are conventional commercially available raw materials or conventional processing techniques in the art.
[0048] Embodiment 1: Weigh 4.210g of quick-release powder (alumina content 95%), add 9.824g of deionized water, stir until dissolved, weigh 61.538g of sodium silicate solution (including SiO 2 The mixture was added with 299.765 g of sulfuric acid solution with a mass concentration of 10% and stirred until uniformly mixed. The mixture was stirred in a 50 °C water bath to gradually form a white sol. The mixture was stirred until the viscosity of the sol reached 1500 mPa·S. The sol was centrifuged and washed until the conductivity of the filtrate was less than 200 μs / cm. The sol was dried at 120 °C to obtain a white powder. 30 g of starch was added to form a ball to obtain a spherical silicon-aluminum composite oxide carrier, which was labeled as SiO 2 -Al 2 O 3 (80-20), which means that the ratio of Si to Al is satisfied. 2 With Al 2 O 3 The total mass is 100%, respectively SiO 2 With Al 2 O 3 The mass ratio of the meter is 80:20, the same below.
[0049] Weigh 6.074 g Cu(NO 3 ) 2 ·3H 2 O, 4.117 g 50 wt% Mn(NO 3 ) 2 solution, 1.261 g Ce(NO 3 ) 3 6H 2 O, using water as solvent, dissolving and stirring evenly to obtain a mixed solution, impregnating the above-mentioned water-resistant silicon-aluminum composite oxide support (mass of about 20g), ultrasonically impregnating for 1h, drying, and heating at 100 o C for 10 h and calcined at 450 ℃ for 4 h to obtain 10%CuO-5%MnO 2 -2.5%CeO 2 / SiO 2 -Al 2 O3 Catalyst, that is, the catalyst is SiO 2 -Al 2 O 3 CuO is the measurement basis of SiO 2 -Al 2 O 3 10% by mass, MnO 2 is 5%, CeO 2 It is 2.5%, the same below.
[0050] Example 2
[0051] Prepare 10%CuO-5%Fe according to the method of Example 1 2 O 3 -2.5%CeO 2 / SiO 2 -Al 2 O 3 catalyst. The difference is that 4.117g 50% Mn(NO 3 ) 2 The solution was replaced with 5.060 g Fe(NO 3 ) 3 9H 2 O.
[0052] Example 3
[0053] Prepare 10%CuO-2.5%MnO according to the method of Example 1 2 -2.5%Fe 2 O 3 -2.5%CeO 2 / SiO 2 -Al 2 O 3 catalyst, the difference is that 50% Mn(NO 3 ) 2 The solution was replaced with 2.058 g 50% Mn(NO 3 ) 2 solution and 2.530 g Fe(NO 3 ) 3 9H 2 O.
[0054] Example 4
[0055] Prepare 10%CuO-5%MnO according to the method of Example 1 2 -2.5%ZnO / SiO 2 -Al 2 O 3 catalyst, the difference is that 1.261g Ce(NO 3) 3 6H 2 O was replaced by 1.827 g Zn(NO 3 ) 2 6H 2 O.
[0056] Example 5
[0057] Prepare 10%CuO-5%Fe according to the method of Example 1 2 O 3 -2.5%ZnO / SiO 2 -Al 2 O 3 catalyst, except that 4.117 g of 50% Mn(NO 3 ) 2 The solution was replaced with 5.060 g Fe(NO 3 ) 3 9H 2 O, 1.261 g Ce(NO 3 ) 3 6H 2 O was replaced by 1.827 g Zn(NO 3 ) 2 6H 2 O.
[0058] Example 6
[0059] Prepare 10%CuO-2.5%MnO according to the method of Example 1 2 -2.5%Fe 2 O 3 -2.5%ZnO / SiO 2 -Al 2 O 3 catalyst, except that 4.117 g of 50% Mn(NO 3 ) 2 The solution was replaced with 2.058 g 50% Mn(NO 3 ) 2 solution and 2.530 gFe(NO 3 ) 3 9H 2 O, 1.261 g Ce(NO 3 ) 3 6H 2 O was replaced by 1.827 g Zn(NO 3 ) 2 6H 2 O.
[0060] Example 7
[0061] Prepare 10%CuO-5%MnO according to the method of Example 1 2 -2.5%ZrO 2 / SiO 2 -Al 2 O 3 catalyst, the difference is that 1.261g Ce(NO 3 ) 3 6H 2 O is replaced by 1.742 g Zr(NO 3 ) 4 ·5H 2 O.
[0062] Example 8
[0063] Prepare 10%CuO-5%Fe according to the method of Example 1 2 O 3 -2.5%ZrO 2 / SiO 2 -Al 2 O 3 catalyst. The difference is that 4.117g 50% Mn(NO 3 ) 2 The solution was replaced with 5.060 g Fe(NO 3 ) 3 9H 2 O, 1.261 g Ce(NO 3 ) 3 6H 2 O is replaced by 1.742 g Zr(NO 3 ) 4 ·5H 2 O.
[0064] Example 9
[0065] Prepare 10%CuO-2.5%MnO according to the method of Example 1 2 -2.5%Fe 2 O 3 -2.5%ZrO 2 / SiO 2 -Al 2 O 3 catalyst, except that 4.117 g of 50% Mn(NO 3 ) 2 The solution was replaced with 2.058 g 50% Mn(NO 3 ) 2 solution and 2.530 gFe(NO 3 ) 3 9H 2O, 1.261 g Ce(NO 3 ) 3 6H 2 O is replaced by 1.742 g Zr(NO 3 ) 4 ·5H 2 O.
[0066] Example 10 Prepare 1%CuO-7.5%MnO according to the method of Example 1 2 -7.5%CeO 2 / SiO 2 -Al 2 O 3 The catalyst is different in that Cu(NO 3 ) 2 ·3H 2 The amount of O used was 0.607 g, 50% Mn(NO 3 ) 2 The amount of solution used is 6.175g, Ce(NO 3 ) 3 6H 2 The amount of O used was 3.783 g.
[0067] Embodiment 11 Prepare 15%CuO-0.5%MnO according to the method of Example 1 2 -0.5%CeO 2 / SiO 2 -Al 2 O 3 The catalyst is different in that Cu(NO 3 ) 2 ·3H 2 The amount of O used is 9.112g, 50% Mn(NO 3 ) 2 The amount of solution used is 0.412g, Ce(NO 3 ) 3 6H 2 The amount of O used was 0.252 g.
[0068] Example 12 Prepare SiO according to the method of Example 1 2 -Al 2 O 3 (96-4) carrier, the difference is that the amount of quick powder removal is 0.842g, the amount of sodium silicate solution is 73.846g, and the amount of 10% H 2 SO 4 The dosage is 321.286g.
[0069] Embodiment 13 Prepare SiO according to the method of Example 1 2 -Al 2 O 3 (90-10) carrier, the difference is that the amount of quick powder removal is 2.105g, the amount of sodium silicate solution is 69.231g, and the amount of 10% H 2 SO 4 The dosage is 313.216g.
[0070] Embodiment 14 Prepare SiO according to the method of Example 1 2 -Al 2 O 3 (70-30) carrier, the difference is that the amount of quick powder removal is 6.316g, the amount of sodium silicate solution is 53.846g, and the amount of 10% H 2 SO 4 The dosage is 286.314g.
[0071] Embodiment 15 Prepare SiO according to the method of Example 1 2 -Al 2 O 3 (60-40) carrier, the difference is that the amount of quick powder removal is 8.421g, the amount of sodium silicate solution is 46.154g, and the amount of 10% H 2 SO 4 The dosage is 272.863g.
[0072] Example 16 Prepare SiO according to the method of Example 1 2 -Al 2 O 3 (50-50) carrier, the difference is that the amount of quick powder removal is 10.526g, the amount of sodium silicate solution is 38.461g, and the amount of 10% H 2 SO 4 The dosage is 259.412g.
[0073] Embodiment 17 Prepare SiO according to the method of Example 1 2 -Al 2 O 3 (80-20) carrier, the difference is that 10%H 2 SO 4 The dosage is 599.529g.
[0074] Embodiment 18 Prepare SiO according to the method of Example 1 2 -Al 2 O 3(80-20) carrier, the difference is that 10%H 2 SO 4 The dosage is 149.882g.
[0075] Comparative Example 1 Weigh 76.923 g of sodium silicate solution (SiO 2 The mixture was stirred in a 50°C water bath to gradually form a transparent sol. The mixture was stirred until the viscosity of the sol reached 1500 mPa·S. The sol was centrifuged and washed until the conductivity of the filtrate was less than 200 μs / cm. The sol was dried at 120°C to obtain a transparent powder. 0.6 g of starch was added to the mixture for rolling ball forming to obtain a spherical silicon oxide carrier, which was labeled as SiO 2 .
[0076] Weigh 6.074 g Cu(NO 3 ) 2 ·3H 2 O, 4.117 g 50 wt% Mn(NO 3 ) 2 solution, 1.261 g Ce(NO 3 ) 3 6H 2 O, using water as solvent, dissolving and stirring evenly to obtain a mixed solution, which is then immersed in the above SiO 2 The carrier (mass about 20g) was ultrasonically impregnated for 1 h, and after drying, it was heated at 100 o C for 10 h and calcined at 450 ℃ for 4 h to obtain 10%CuO-5%MnO 2 -2.5%CeO 2 / SiO 2 catalyst.
[0077] Comparative Example 2 Weigh 21.053 g of quick-release powder (alumina content of 95%), add 49.124 g of deionized water, stir until dissolved, add 192.157 g of 10% sulfuric acid solution dropwise, stir in a 50 °C water bath, gradually form a white sol, continue stirring until the sol viscosity reaches 1500 mPa·S, centrifuge and wash the sol until the conductivity of the filtrate is less than 200 μs / cm, dry at 120 °C to obtain a white powder, add 0.6 g of starch for rolling ball forming, and obtain a spherical alumina carrier, marked as Al 2 O 3 .
[0078] Weigh 6.074 g Cu(NO 3 ) 2·3H 2 O, 4.117 g 50 wt% Mn(NO 3 ) 2 solution, 1.261 g Ce(NO 3 ) 3 6H 2 O, using water as solvent, dissolve and stir evenly to obtain a mixed solution, which is then immersed in the above Al 2 O 3 The carrier (mass about 20g) was ultrasonically impregnated for 1 h, and after drying, it was heated at 100 o C for 10 h and calcined at 450 ℃ for 4 h to obtain 10%CuO-5%MnO 2 -2.5%CeO 2 / Al 2 O 3 catalyst.
[0079] Comparative Example 3 Prepare 10% CuO / SiO according to the method of Example 1 2 -Al 2 O 3 catalyst. The difference is that 50% Mn(NO 3 ) 2 Solution and Ce(NO 3 ) 3 6H 2 The dosage of O is 0.
[0080] Comparative Example 4 Prepare 10%CuO-5%MnO according to the method of Example 1 2 / SiO 2 -Al 2 O 3 catalyst. The difference is that Ce(NO 3 ) 3 6H 2 The dosage of O is 0.
[0081] Comparative Example 5 Prepare 10%CuO-5%Fe according to the method of Example 1 2 O 3 / SiO 2 -Al 2 O 3 catalyst. The difference is that 4.117g 50% Mn(NO 3 ) 2 The solution was replaced with 5.060 g Fe(NO 3 ) 3 9H 2 O,Ce(NO 3 )3 6H 2 The dosage of O is 0.
[0082] Comparative Example 6 Prepare 10%CuO-2.5%CeO according to the method of Example 1 2 / SiO 2 -Al 2 O 3 catalyst. The difference is that 50%Mn(NO 3 ) 2 The solution dosage is 0, Ce(NO 3 ) 3 6H 2 The amount of O used was 1.261 g.
[0083] Comparative Example 7 Prepare 10%CuO-2.5%ZnO / SiO according to the method of Example 1 2 -Al 2 O 3 catalyst. The difference is that 50%Mn(NO 3 ) 2 The amount of solution is 0, 1.261g Ce(NO 3 ) 3 6H 2 O was replaced by 1.827 g Zn(NO 3 ) 2 6H 2 O.
[0084] Comparative Example 8 Prepare 10%CuO-2.5%ZrO according to the method of Example 1 2 / SiO 2 -Al 2 O 3 catalyst. The difference is that 50%Mn(NO 3 ) 2 The amount of solution is 0, 1.261g Ce(NO 3 ) 3 6H 2 O is replaced by 1.742 g Zr(NO 3 ) 4 ·5H 2 O.
[0085] Comparative Example 9 Prepare SiO according to the method of Example 1 2 -Al 2 O 3(40-60) carrier, the difference is that the amount of quick powder removal is 12.632g, the amount of sodium silicate solution is 30.769g, and the amount of 10% H 2 SO 4 The dosage is 245.961g.
[0086] Comparative Example 10 Prepare 15%CuO-2.5%CeO according to the method of Example 1 2 / SiO 2 -Al 2 O 3 catalyst. The difference is that Cu(NO 3 ) 2 ·3H 2 The amount of O used was 9.112 g, 50% Mn(NO 3 ) 2 The amount of solution used is 0.
[0087] Comparative Example 11 Prepare 11.5%CuO-6%MnO according to the method of Example 1 2 / SiO 2 -Al 2 O 3 catalyst. The difference is that Cu(NO 3 ) 2 ·3H 2 The amount of O used is 6.986 g, 50% Mn(NO 3 ) 2 The amount of solution used is 4.940 g, Ce(NO 3 ) 3 6H 2 The dosage of O is 0.
[0088] The characterization data of the carriers in each embodiment and comparative example are shown in Table 1.
[0089] Among them, the specific surface area and pore volume are obtained by BET test; the strength is obtained by strength tester test.
[0090] Table 1 Characterization data of carriers
[0091] It can be seen from Table 1 that in Comparative Example 1, SiO 2 Although the carrier has a higher specific surface area and pore volume, the particle breakage rate is as high as 83% when it encounters liquid water, and after 550 o After the water vapor treatment, the particle strength decreased significantly (by 59.3%), which may cause powderization in industrial applications, increase pressure drop, and affect normal use. 2 O 3The specific surface area and pore volume of the carrier are both low. At the same time, the particle breakage rate when encountering liquid water is 1.5%. o After the water vapor treatment, the particle strength decreased by 24.5%; compared with Comparative Example 2, the specific surface area and pore volume of the silicon-aluminum composite oxide carrier prepared in the embodiment are significantly greater than those of Al 2 O 3 carrier, and the breakage rate when encountering liquid water is less than 1%. o After C water vapor treatment, the particle strength decreases by less than 10%, and the performance is significantly better than Al 2 O 3 Carrier. It can be seen from Examples 1, 12-16 and Comparative Example 9 that with the increase of silicon content, the specific surface area and pore volume of the silicon-aluminum composite oxide carrier increase. In Examples 1 and 17-18, the amount of sulfuric acid was changed, among which the amount of sulfuric acid in Example 18 was the lowest, the amount in Example 17 was the highest, and Example 1 was in the middle. It can be seen from Examples 1, 17 and 18 that the increase in the amount of sulfuric acid helps to increase the specific surface area and pore volume of the silicon-aluminum composite oxide carrier, but has an impact on the breakage rate and 550% pore volume when encountering liquid water. o C The water vapor treatment has little effect on the change of particle strength.
[0092] Figure 1 is the CO of the carrier in the examples and comparative examples 2 -TPD spectrum. Figure 1 It can be seen that with Al 2 O 3 Compared with the carrier, SiO 2 The alkalinity on the support is relatively weak, but the number of weak base sites is significantly higher than that of Al 2 O 3 . With SiO 2 Compared with the carrier, as the silicon oxide content decreases, the alkalinity of the weak base sites on the silicon-aluminum composite oxide carrier gradually increases, but the number of weak base sites gradually decreases. At the same time, the alkalinity of the medium-strong base sites gradually weakens, thereby forming a large number of alkaline sites with moderate alkalinity. 2 During the catalytic conversion reaction, CO 2 Adsorption is the first step, and alkaline sites with moderate alkalinity and a large number of them help promote CO 2 The adsorption of CO with silicon-aluminum composite oxide supports is moderate, thus promoting the 2 Adsorption and catalytic conversion help improve CO 2 Conversion rate.
[0093] The characterization and performance evaluation data of the catalysts in each embodiment and comparative example are shown in Table 2.
[0094] Among them, the specific surface area, pore volume and pore size were obtained by BET test; the CuO grains were obtained by XRD test, and the CO2 The conversion rate and CO selectivity were obtained from the performance evaluation test of the catalyst.
[0095] Table 2 Characterization and evaluation data of catalysts
[0096] It can be seen from Table 2 that with SiO 2 -Al 2 O 3 Compared with the (80-20) carrier, after the metal is loaded, the specific surface area and pore volume of the catalyst in Example 1-11 are reduced to a certain extent. This is because the metal covers a part of the surface of the silicon-aluminum composite oxide carrier and blocks part of the pores.
[0097] Figure 2 The XRD spectra of the catalyst and the carrier in Example 1 and Comparative Examples 3, 4 and 6 are shown in FIG. Figure 2 It can be found that 2θ=23.5 o The diffraction peak at is attributed to amorphous aluminum silicate (SiO 2 -Al 2 O 3 Carrier). When 10% CuO is loaded on the carrier, 2θ=35.5 o , 38.8 o There is an obvious CuO characteristic diffraction peak at the 2 After that, 2θ=28.6 o , 47.8 o There is obvious CeO 2 Characteristic diffraction peak. 10%CuO / SiO 2 -Al 2 O 3 With 10%CuO-5%MnO 2 / SiO 2 -Al 2 O 3 By comparing the XRD spectra of 2 , significantly reducing the characteristic diffraction peak of CuO, which indicates that the second active component MnO 2 It effectively promotes the high dispersion of the first active component CuO on the carrier surface and helps to reduce the CuO grain size (as shown in Table 2). 2 / SiO 2 -Al 2 O 3 、10%CuO-2.5%CeO 2 / SiO 2 -Al 2 O 3、10%CuO-5%MnO 2 -2.5%CeO 2 / SiO 2 -Al 2 O 3 By comparing the XRD spectra of CeO 2 After adding the additive, 10%CuO-5%MnO 2 -2.5%CeO 2 / SiO 2 -Al 2 O 3 CuO and CeO are not observed in the XRD spectrum. 2 The characteristic diffraction peaks of CeO 2 Under the promotion of additives, CuO and CeO 2 A uniform solid solution structure is formed, which further improves the dispersion of CuO and reduces the CuO grain size (as shown in Table 2), which helps to stabilize the first active component CuO and thus improve the stability of the catalyst.
[0098] Figure 3 is the H of the catalyst in Example 1, Comparative Examples 3, 4, and 6 2 -TPR spectrum. 10%CuO / SiO 2 -Al 2 O 3 With 10%CuO-2.5%CeO 2 / SiO 2 -Al 2 O 3 H 2 -TPR spectrum comparison shows that CeO 2 The addition of additives significantly reduces the reduction temperature and improves the reduction performance of CuO. o A shoulder peak appeared around C, which indicated that CeO 2 After the additive is added, the amount of CuO highly dispersed on the surface is greatly increased, thereby reducing the reduction temperature of CuO. 2 -Al 2 O 3 With 10%CuO-5%MnO 2 / SiO 2 -Al 2 O 3 H 2 -TPR spectrum comparison shows that due to MnO 2 The reduction temperature of CuO is higher than that of CuO. Therefore, when the second active component MnO is added 2 After that, CuO and MnO 2 The synergistic effect between them leads to 10%CuO-5%MnO2 / SiO 2 -Al 2 O 3 The catalyst reduction temperature slightly moved toward high temperature. Combined with the XRD results, it can be concluded that the electronic effect between Cu and Mn caused the valence distribution of Cu on the catalyst surface to change, resulting in a high dispersion of Cu on the catalyst surface. 2 / SiO 2 -Al 2 O 3 With 10%CuO-5%MnO 2 -2.5%CeO 2 / SiO 2 -Al 2 O 3 H 2 -TPR spectrum comparison further verifies the CeO 2 The addition of additives can significantly reduce the reduction temperature, promote the reduction of CuO, and improve the reduction performance of the catalyst. 2 The addition of CuO and MnO 2 The electronic effect between Cu and Mn optimizes the valence distribution of Cu on the catalyst surface and improves the dispersion. 2 The addition of helps to improve the reduction performance of the catalyst, increase the number of highly dispersed CuO species on the surface, and lower the reduction temperature.
[0099] CO 2 Catalytic conversion performance test A stainless steel tube fixed bed reactor was used to carry out CO 2 Catalytic conversion performance evaluation: the process conditions used for evaluation are: catalyst loading 1mL, feed gas composition 10%CO 2 -30%H 2 -60%Ar, reaction temperature is 300 o C, gas phase space velocity is 12000h -1 The product was analyzed online by gas chromatography GC2060, and the activity evaluation results are shown in Table 2.
[0100] According to Table 2, CO 2 The data of conversion rate and CO selectivity are compared with Example 1 and Comparative Examples 1-2, and it can be found that compared with 10% CuO-5% MnO 2 -2.5%CeO 2 / SiO 2 、10%CuO-5%MnO 2 -2.5%CeO 2 / Al2 O 3 Compared with 10%CuO-5%MnO 2 -2.5%CeO 2 / SiO 2 -Al 2 O 3 The catalyst has a higher CO 2 Conversion and CO selectivity, combined with the support's CO 2 -TPD data show that SiO 2 The alkalinity of the carrier is weak, Al 2 O 3 The alkalinity is relatively strong, while SiO 2 -Al 2 O 3 The composite carrier has moderate alkaline sites and more alkaline sites, so SiO 2 -Al 2 O 3 Composite carrier is more conducive to CO 2 Adsorption and conversion promote the efficient conversion of intermediate products into the target product CO, thereby increasing CO 2 Conversion rate and CO selectivity. Comparison of Comparative Examples 3-8 shows that compared with 10% CuO / SiO 2 -Al 2 O 3 Compared with the catalyst, the addition of the second active component and the additive, CO 2 The conversion rate and CO selectivity were improved to varying degrees. Among them, the second active component MnO 2 、CeO additive 2 By comparing Examples 1-9 and Comparative Examples 4-6, it can be found that when the second active component and the auxiliary agent are present at the same time, the CO on the catalyst 2 The conversion rate and CO selectivity will be higher, especially 10%CuO-5%MnO 2 -2.5%CeO 2 / SiO 2 -Al 2 O 3 Catalyst, at 300 o C, CO 2 The conversion rate reached 23.08%, close to the thermodynamic equilibrium value, and the CO selectivity was 100%.
[0101] Figure 4 The in-situ infrared spectra of the catalysts in Example 1 and Comparative Examples 3, 4 and 6 are shown in FIG. Figure 4 From the data of CO selectivity in Table 2, it can be found that 10%CuO / SiO 2 -Al 2 O3 In addition to the product CO, there are also intermediate products such as formic acid, carboxylates, carbonates, and methane by-products on the catalyst, while 10%CuO-5%MnO 2 / SiO 2 -Al 2 O 3 and 10%CuO-2.5%CeO 2 / SiO 2 -Al 2 O 3 The catalyst only has a weak methane byproduct, 10%CuO-5%MnO 2 -2.5%CeO 2 / SiO 2 -Al 2 O 3 No byproducts or intermediates were observed on the catalyst, only the target product CO. This indicates that the second active component MnO 2 and CeO 2 The addition of additives effectively promotes the timely conversion of intermediate products into the target product CO and inhibits the formation of CO at low temperatures. 2 Methanation side reaction significantly increases CO 2 Conversion and CO selectivity.
[0102] CO under different reaction conditions 2 Catalytic conversion performance test The catalyst in Example 1 was subjected to CO 2 The catalytic conversion performance was evaluated under the following process conditions: the catalyst loading was 1 mL, CO 2 The concentration is 10%, the reaction pressure is 0.1~2.0MPa, and the reaction temperature is 300~550 o C, gas phase space velocity is 3000~24000h -1 , H 2 / CO 2 The product was analyzed online by gas chromatography GC2060, and the activity evaluation results are shown in Table 3.
[0103] Table 3 Catalyst performance evaluation data in Example 1
[0104] It can be seen from Table 3 that the 10%CuO-5%MnO in Example 1 2 -2.5%CeO 2 / SiO 2 -Al 2 O 3 Catalyst, as the reaction temperature increases, CO 2The conversion rate showed an increasing trend, which was due to the 2 The reverse water-gas shift reaction process is endothermic, and increasing the temperature helps to increase the CO 2 Conversion rate; increasing reaction pressure, CO 2 The conversion rate is slightly improved, but a small amount of methane by-product will be produced; the reaction space velocity is 2 The conversion rate and CO selectivity were less affected; with the increase of H 2 / CO 2 The increase in CO 2 The conversion rate increased slightly, and the CO selectivity remained at 100%.
[0105] Catalyst stability performance test The stability performance of the catalyst in Example 1 was evaluated using a stainless steel tube fixed bed reactor. The process conditions used for the evaluation were: the catalyst loading was 1 mL, the feed gas was 10% CO 2 -30%H 2 -60%Ar, reaction pressure is normal pressure, reaction temperature is 550 o C, gas phase space velocity is 12000h -1 The product was analyzed online by gas chromatography GC2060, and the activity evaluation results were as follows: Figure 5 shown.
[0106] Depend on Figure 5 It can be seen that within 500h of continuous reaction, 10%CuO-5%MnO 2 -2.5%CeO 2 / SiO 2 -Al 2 O 3 CO on catalyst 2 The conversion rate was maintained at about 54%, the CO selectivity was always close to 100%, the stability was good, and there was no deactivation phenomenon. Combined with the in situ infrared results, it can be concluded that in the 10% CuO-5% MnO 2 -2.5%CeO 2 / SiO 2 -Al 2 O 3 On the catalyst, CO 2 It can efficiently adsorb and catalyze the conversion in time. The intermediate products in the reaction process can be quickly converted into the target product CO. It does not occupy the active sites of the catalyst, does not block the pores of the catalyst, and no methanogenic side reactions occur. This allows the active sites of the catalyst to remain stable for a long period of time, greatly improving the stability of the catalyst.
[0107] In summary, the CO 2Catalytic conversion catalyst, wherein the water-resistant silicon-aluminum composite oxide carrier has a large specific surface area and a large pore volume, which is conducive to the high dispersion of active components, reduces the grain size of active components, inhibits the aggregation and growth of active components, and thus improves the stability of the catalyst; at the same time, the water-resistant silicon-aluminum composite oxide carrier can withstand liquid water, prevent a small amount of liquid water in industrial applications from causing the catalyst to pulverize, causing an increase in pressure drop, and thus improve the stability of industrial device operation; in addition, the water-resistant silicon-aluminum composite oxide carrier has good high thermal stability and water resistance, which improves the stability of the catalyst under high temperature and high humidity conditions and prolongs the service life. On the basis of the first active component CuO, the second active component is introduced to form a synergistic effect between the two active components, and the electronic effect between the two changes the valence distribution of Cu, promotes the improvement of CuO dispersion, reduces the CuO grain size, and improves the catalytic activity; after the introduction of the auxiliary agent, the auxiliary agent forms a solid solution structure with CuO, further improves the dispersion of CuO, reduces the CuO grain size, and at the same time plays a role in stabilizing CuO and improving the stability of the catalyst. In addition, the addition of the auxiliary agent effectively reduces the reduction temperature of the catalyst, increases the amount of highly dispersed CuO on the surface, and thus improves the low-temperature activity of the catalyst. The addition of the second active component and the additive promotes the efficient conversion of intermediate products (formic acid, carboxylates, carbonates, etc.) into the target product CO, and also effectively inhibits the CO 2 The methanogenic side reaction can greatly improve the high temperature stability of the catalyst. 2 The catalytic conversion catalyst has a simple preparation process and low production cost, which is conducive to industrial production and application. It has significant economic advantages and broad prospects for industrial application.
[0108] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a CO2 catalytic conversion catalyst, characterized in that: The following steps are involved: (1) Weigh a silicon source and an aluminum source to prepare a silicon-aluminum aqueous solution, mix it with an inorganic acid aqueous solution, and stir to form a white sol until the viscosity reaches 1200-2000 mPa·S; (2) centrifuging, washing and drying the sol obtained in step (1) to obtain white silicon-aluminum composite oxide powder, adding a binder and rolling into balls to obtain a silicon-aluminum composite oxide carrier precursor; (3) Weighing a first active component precursor, a second active component precursor and an auxiliary component precursor, dissolving and stirring them with water as a solvent to obtain a mixed solution; (4) impregnating the silicon-aluminum composite oxide support precursor in step (3) in the mixed solution, drying, and calcining to obtain a CO2 catalytic conversion catalyst; In step (1), the H + , the molar ratio of the total amount of SiO2+Al2O3 in the silicon source and the aluminum source is 0.5~2:1; The CO2 catalytic conversion catalyst includes a silicon-aluminum composite oxide support, and a first active component, a second active component and an auxiliary component loaded on the silicon-aluminum composite oxide support, wherein the first active component is CuO, the second active component is an oxide of Mn and / or Fe, and the auxiliary component is an oxide of at least one of Ce, Zr or Zn, wherein the mass content of SiO2 in the silicon-aluminum composite oxide support is 50% to 80%, and the mass content of Al2O3 is 20% to 50%; the first active component is 1 to 15% of the mass of the silicon-aluminum composite oxide support, the second active component is 0.5 to 7.5% of the mass of the silicon-aluminum composite oxide support, and the auxiliary component is 0.5 to 7.5% of the mass of the silicon-aluminum composite oxide support.
2. The method for preparing a CO2 catalytic conversion catalyst according to claim 1, characterized in that: In step (1), the silicon source is selected from one or more of silica sol, sodium silicate, and silicon oxide powder; The aluminum source is selected from one or more of aluminum sol, pseudo-boehmite, quick-de-powder, and alumina powder; The inorganic acid is one or more of nitric acid, hydrochloric acid or sulfuric acid.
3. The method for preparing a CO2 catalytic conversion catalyst according to claim 1, characterized in that: In step (2), washing is performed once or repeatedly for multiple times until the conductivity of the filtrate is less than 200 μs / cm; The drying temperature is 100~120℃; The mass ratio of white silicon-aluminum composite oxide powder to binder is 1:(0.005-0.05), and the binder is one or more of silica sol, aluminum sol, bentonite, sodium methyl cellulose, starch, attapulgite, and kaolin.
4. The method for preparing a CO2 catalytic conversion catalyst according to claim 1, characterized in that: In step (3), the first active component precursor is copper nitrate; The second active component precursor is a nitrate of Mn and / or Fe; The auxiliary agent component precursor is nitrate of Ce and / or Zr.
5. The method for preparing a CO2 catalytic conversion catalyst according to claim 1, characterized in that: In step (4), the immersion process is specifically as follows: ultrasonic immersion for 0.5 to 2 h; The specific drying process is as follows: drying at 100-120 °C for 6-12 h; The specific calcination process is: calcination at 350~600 ℃ for 2~6 h.
6. A CO2 catalytic conversion catalyst, characterized in that: It is prepared based on the preparation method according to any one of claims 1 to 5, and the specific surface area of the catalyst is 350 to 650 m 2 / g, pore volume is 0.3~0.7 cm 3 / g, CuO grain size is less than 2nm.
7. Application of a CO2 catalytic conversion catalyst in CO2 reverse water gas shift reaction, characterized in that: The CO2 catalytic conversion catalyst as claimed in claim 6 is used.
Citation Information
Patent Citations
Supported non-noble metal oxygen-containing coalbed methane deoxidation catalyst and preparation method and application thereof
CN102872883A
A noble metal catalyst used for a reverse water gas shift reaction, and preparation and applications of the catalyst
CN106881084A
Methods for preparing high temperature water gas shifting catalyst, catalyst and process for reducing carbon monoxide
GB202114357D0
Molded body of carbon dioxide methanation catalyst and method for producing the same
WO2022224993A1
Cited By
High-strength reverse shift reaction catalyst and preparation method thereof
CN121016845A